2014
DOI: 10.1039/c4ta03997a
|View full text |Cite
|
Sign up to set email alerts
|

Polyolefin based antibacterial membranes derived from PE/PEO blends compatibilized with amine terminated graphene oxide and maleated PE

Abstract: In this study, various strategies like amine terminated GO (GO-NH 2 ), in situ formed polyethylene grafted GO (PE-g-GO) and their combinations with maleated PE (maleic anhydride grafted PE) were adopted to reactively compatibilize blends of low density polyethylene (LDPE) and polyethylene oxide (PEO). These blends were further explored to design porous, antibacterial membranes for separation technology and the flux and the resistance across the membranes were studied systematically. It was observed that GO-NH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 107 publications
(72 citation statements)
references
References 40 publications
(57 reference statements)
0
70
0
Order By: Relevance
“…34 For instance, in a recent study on PE/PEO blends with GO-NH 2 the antibacterial efficiency of the membrane was attributed to the ROS (reacting oxygen species) and physical damage induced by the rough GO surface. 29 From SEM images, we can conclude that PVDF/PMMA membranes with Ag@TiO 2 -CNTs have good antifouling and antibacterial properties. For quantitative analysis, the standard plate count method was employed and the details are mentioned in the Experimental section.…”
Section: Antibacterial and Antifouling Properties Of The Membranesmentioning
confidence: 97%
“…34 For instance, in a recent study on PE/PEO blends with GO-NH 2 the antibacterial efficiency of the membrane was attributed to the ROS (reacting oxygen species) and physical damage induced by the rough GO surface. 29 From SEM images, we can conclude that PVDF/PMMA membranes with Ag@TiO 2 -CNTs have good antifouling and antibacterial properties. For quantitative analysis, the standard plate count method was employed and the details are mentioned in the Experimental section.…”
Section: Antibacterial and Antifouling Properties Of The Membranesmentioning
confidence: 97%
“…The synthesis and characterization of MDA−GO have already been reported in our earlier study. 38 Upon grafting of MDA onto GO sheets, the band around 1000−1150 cm −1 becomes broader indicating the nucleophilic substitution reaction at the epoxy groups. Furthermore, the presence of C−OH and C−N bonds is confirmed by the bands present in the range of 1000−1300 cm −1 , as shown in Figure 2.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Primary, Secondary, and Tertiary Amines: Many studies have been reported on the use of amine derivatives like chitosan, [100][101][102][103][104][105] polyethylenimine (PEI), [106][107][108][109] guanidine, [110][111][112][113] and dopamine [114][115][116][117] for antibacterial and antifouling applications. After protonation in the presence of water, these derivatives exhibit a net positive charge.…”
Section: Aminesmentioning
confidence: 99%